Digestion and ruminal fermentation of cocoa pod silage based ration enriched by gliricidia and calliandra leaves on goats - W, Puastuti; Y, Widiawati; E, Wina (Indonesian Journal of Animal and Veterinary Sciences, 2015)
In term of availability, cacao pod is potential for ruminant feed. According to the nutrients content, cacao pod can be used as fiber source feed. Protein sources materials must be combined when cacao pod was ensilage due to low protein content of this material. The aim of study was to investigate digestibility value and end products of rumen fermentation of goat fed by grass or cacao pod based ration. The study used randomized block design to 20 lambs (16.95 ± 2.36 kg) to evaluated 5 type of rations: R (50% grass + 50% concentrate); S (50% cacao pod silage + 50% concentrate); SG (50% cacao pod-gliricidia silage + 50% concentrate); SK (50% cacao pod-calliandra silage + 50% concentrate) dan SC (50% cacao pod-mixture of gliricidia-calliandra silage + 50% concentrate). Feeding trial was conducted over 15 weeks. Measurements were undertaken on feed digestibility and rumen-fermentation end-products after 3 weeks of the animals treated by treatmets rations. Results shows that nutrients digestibility was different significantly among the groups of treatments (P<0.05). Digestibillity of organic matter, NDF and energy of R ration was higher significantly (P<0.05) than those of other groups. N-ammonia of rumen from goat feed R ration was higher (P<0.05) than other groups. Total VFA and each component were different among the groups (P<0.05), however the value was similar among the groups of cacao pod silage rations. It is concluded that cacao pod silaged based rations enriched by Gliricidia and Calliandra leaves did not produced similar digestibility value and end products of rumen fermentation with grass based ration.Key Words: Cacao Pod Silage, Digestibility, Ruminal Fermentation